Nonlinear Parabolic Equations with Singular Coefficient with Respect to the Unknown and with Diffuse Measure Data (Journal of Partial Differential Equations, 2020)
An existence and uniqueness result of a renormalized solution for a classof doubly nonlinear parabolic equations with singular coefficient with respect to theunknown and with diffuse measure data is established. A comparison result is alsoproved for such solutions.